The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00405-010-1284-1
|View full text |Cite
|
Sign up to set email alerts
|

Transoral CO2 laser microsurgery for Tis-T3 supraglottic squamous cell carcinomas

Abstract: Eighty patients affected by supraglottic cancer were treated by transoral carbon dioxide laser surgery between 1989 and 2006 in two Italian institutions. Patient staging was as follows: 2 pTis, 20 pT1, 38 pT2, and 20 pT3. Simultaneous or 1-month delayed neck dissection (ND) was performed on 27 (34%) patients, unilaterally in 10 and bilaterally in 17. The pN category was as follows: 9 pN0, 6 pN1, 8 pN2b, and 4 pN2c. A total of 16 (20%) patients received complementary radiotherapy (RT) and 5 (6%) were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 21 publications
2
61
0
2
Order By: Relevance
“…In this perspective, post-operative irradiation has been reported to increase the rate of laryngeal preservation [35], accordingly to its previous mentioned indications. However, adjuvant RT is usually discouraged on the primary tumour site after partial laryngeal surgery because of its potential unfavourable functional late effects, including its rate in delaying patients recovery.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In this perspective, post-operative irradiation has been reported to increase the rate of laryngeal preservation [35], accordingly to its previous mentioned indications. However, adjuvant RT is usually discouraged on the primary tumour site after partial laryngeal surgery because of its potential unfavourable functional late effects, including its rate in delaying patients recovery.…”
Section: Discussionmentioning
confidence: 83%
“…The lowest DFS rate was 52.54% [32], with other two studies both reporting 93.75% of DFS [33,42] and one study showing no recurrence event [35]. The forest plot is shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The 5-year recurrence-free survival rate was 71%. Peretti et al 27 reported on a series of 80 patients treated with laser microsurgery in which 20 patients with pT3 lesions showing "limited infiltration" of the preepiglottic fat. In 88.2% of patients larynx preservation was achieved, the 5-year disease-free survival was 59.6%.…”
Section: Oncologic Resultsmentioning
confidence: 99%